"Welcome to My Kingdom": The Therapy Process between an Adolescent and a Dance Movement Therapist in Training. (2nd January 2021) - Demirtoka, Sezin
ABSTRACT: This case study explores issues of depression, body image, attachment and suicidality in the context of dance movement therapy with an adolescent boy. Specifically, it looks to investigate the nonverbal aspects of the emerging therapeutic relationship and the use of experiential techniques as a means of creating a secure base where the patient can freely explore and share his inner world with the therapist. The therapy process took place between the author, who was at the time a trainee in dance movement therapy, and an eighteen year old boy attending a day hospital after a suicide attempt. The process is presented through the description of the sessions, with a specific focus on the intersubjective movement experience shared by the therapist and patient, and its relation to the patient's emotional strugglings. Selected drawings by the patient are also presented, as drawing played a key role in the sessions.